(untitled) (Medical Forum Monthly, 2021)
Objective: To study the Incidence of Hepatitis in Pregnant Women Study Design: Retrospective Study Place and Duration of Study: This study was conducted at the Mansehra Teaching Hospital Abbottabad, PAF Hospital Islamabad from 1st March, 2018 to 28th February, 2020. Materials and Methods: Four hundred reproductive age pregnant females of group from King Abdullah Teaching Hospital Mansehra and PAF Hospital Islamabad were selected by sampling technique were studied at Mansehra teaching hospital Mansehra and PAF Hospital Islamabad,) The permission of Ethical Committee was taken before collection of data and get publishing in medical journal. Results: The incidence of hepatitis was maximum 197 (49.25%) at age group 15-25 years and minimum 12 (3.0%) at age group 37-45 years. The incidence of hepatitis was maximum 220 (55%) in District Mansehra & was 180 (45%) in District Sialkot respectively. The incidence of hepatitis was maximum was maximum 190 (47.5%) in Low class of pregnant women & minimum 70 (17.5%) in high gentry of pregnant women. The incidence of hepatitis was maximum at 2nd trimester 170 (42.5%) & minimum at 1st trimester 102 (25.5%). The frequency subjected to ALT & ICT was maximum 175 (43.75%) in discarded after initial testing & was minimum 15 (3.75%) in repeated after 4 weeks. The incidence of hepatitis was maximum at initial screening by ICT positive patients 70 (17.5%) & negative patients 330 (85.5%). The incidence of hepatitis was maximum 80 (50.63%) every 5th sample -ve for HCV by ICT, was minimum 30 (7.5%) sample with high ALT of ELISA tests for HCV antibodies. The incidence of hepatitis C patients was 297 (74.25%) & Hepatitis B Patients was 103 (25.75%) respectively. Conclusion: Seroprevalence of HCV in pregnant females of District Mansehra & District Sialkot different from the figures already reported from the other parts of Pakistan.